2015
DOI: 10.1128/aac.04677-14
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Outcomes with Cefazolin versus Oxacillin for Deep-Seated Methicillin-Susceptible Staphylococcus aureus Bloodstream Infections

Abstract: Despite the rise and impact of methicillin-resistant Staphylococcus aureus, methicillin-susceptible S. aureus (MSSA) continues to contribute to the overall burden of S. aureus infections, representing Ն50% of clinical S. aureus strains (1-3) with known appreciable mortality outcomes (4, 5). Prevailing evidence supports the use of semisynthetic penicillins, such as oxacillin or nafcillin, or the first-generation cephalosporin cefazolin in preference to vancomycin as optimal therapy for MSSA bloodstream infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 24 publications
5
45
1
2
Order By: Relevance
“…Efficacy data from recent retrospective studies comparing antistaphylococcal penicillins to cefazolin for treatment of MSSA BSI are conflicting. Similar to the results of our study, several other retrospective studies have suggested that cefazolin and antistaphylococcal penicillin agents may have similar efficacy in the treatment of MSSA BSI [6-9]. Others have even suggested a treatment benefit with cefazolin over antistaphylococcal penicillins [17, 24].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Efficacy data from recent retrospective studies comparing antistaphylococcal penicillins to cefazolin for treatment of MSSA BSI are conflicting. Similar to the results of our study, several other retrospective studies have suggested that cefazolin and antistaphylococcal penicillin agents may have similar efficacy in the treatment of MSSA BSI [6-9]. Others have even suggested a treatment benefit with cefazolin over antistaphylococcal penicillins [17, 24].…”
Section: Discussionsupporting
confidence: 81%
“…Patients were classified into a nafcillin arm or a cefazolin arm based on the initial choice of directed therapy. Similar to a previous study, transition between study agents was not considered a treatment failure, and patient outcomes were assessed according to their initial treatment regimen [6]. Baseline patient characteristics and treatment parameters were compared between treatment groups using the Student t test and Kruskal-Wallis test for continuous variables, and the Fisher’s exact test for categorical variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent retrospective studies have suggested that cefazolin had outcomes comparable to those of antistaphylococcal penicillins such as nafcillin and oxacillin (1,(17)(18)(19), even for serious infections. However, there are concerns about cefazolin therapeutic failures and relapses in the treatment of MSSA strains that demonstrate the CIE (2,3,20,21).…”
mentioning
confidence: 99%